FIXATION [CONGESTION] OF CHILDREN IN COMPREHENDING LEARNING - Yola Pradita; Pilenia Pilenia; Olivtia Kesia Pebriany; Daniel NP Simatupang; Restiani Restiani; Reynhard Malau; Maria Veronica (CV. ADIBA AISHA AMIRA, 2023)
This research aims to explore the factors that cause children's fixation or bottlenecks in understanding learning both at school and at home. This research method is qualitative using interview techniques and collecting materials in the form of scientific journals. In this research, researchers found several important things from journals and also responses from sources regarding factors that could cause fixation or learning bottlenecks in children, such as attention disorders for example due to the use of social media or electronic devices, the quality of teachers, difficulties in reading, children those with special needs, children who lack self-confidence, learning techniques, poor sleep quality, stress, fatigue, school environmental factors that are less conducive, the role of parents in educating and guiding children, and many more. Researchers also found several solutions from sources regarding what solutions could be taken when children experience fixations or bottlenecks in understanding learning. Researchers conducted qualitative research using interview methods with students and people who were already wor.